Multikulturalisme dalam Pembelajaran Sejarah: Perpektif Mahasiswa Generasi Z - Firdaus Hadi Santosa; Umasih Umasih; Muhammad Hasmi Yanuardi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
This study aims to reveal the perspectives of generation z students on aspects of multiculturalism in history learning, related to the importance of learning history as a means of cultivating multiculturalism that serves to maintain the integrity and unity of the pluralistic Indonesian nation. The research method used is a qualitative method with a case study approach, with 20 z-generation history education study program students as informants. Data collection was done through in-depth interviews, observation, and document review. The results showed that informants have a positive view of the application of multiculturalism in history learning, informants are also optimistic about applying multiculturalism in history learning, although there are shortcomings and obstacles in applying it due to time constraints and multiculturalism content in history learning materials. The conclusion is that z-generation students have a positive perspective and are optimistic about the application of multiculturalism in history learning, as well as understanding the limitations of its application and feel the need to make innovations in its application.